2012
DOI: 10.1056/nejmc1111038
|View full text |Cite
|
Sign up to set email alerts
|

Machine Perfusion or Cold Storage in Deceased-Donor Kidney Transplantation

Abstract: BACKGROUNDStatic cold storage is generally used to preserve kidney allografts from deceased donors. Hypothermic machine perfusion may improve outcomes after transplantation, but few sufficiently powered prospective studies have addressed this possibility. METHODSIn this international randomized, controlled trial, we randomly assigned one kidney from 336 consecutive deceased donors to machine perfusion and the other to cold storage. All 672 recipients were followed for 1 year. The primary end point was delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
298
4
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 324 publications
(322 citation statements)
references
References 3 publications
12
298
4
8
Order By: Relevance
“…Following recent studies showing the beneficial effect of MP over CS preservation of deceased kidney grafts, MP holds the potential for a true comeback. 6,8,10,17 In the first large multi-center, prospective, randomized clinical trial performed by Moers et al, 17 it was demonstrated that kidney grafts from standard as well as extended criteria donors benefit from MP as the risk of delayed graft function was significantly reduced.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Following recent studies showing the beneficial effect of MP over CS preservation of deceased kidney grafts, MP holds the potential for a true comeback. 6,8,10,17 In the first large multi-center, prospective, randomized clinical trial performed by Moers et al, 17 it was demonstrated that kidney grafts from standard as well as extended criteria donors benefit from MP as the risk of delayed graft function was significantly reduced.…”
Section: Discussionmentioning
confidence: 98%
“…The rationale of lowering the PP originates from the common regard that pressure induced endothelial damage is one of the main drawbacks associated with MP. 3,9,17 Also, the feasibility of the new perfusion solution POLYSOL was evaluated. By using a similar experimental model as Maathuis et al, parameters of microcirculatory integrity, renal function and morphology were assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 A meta-analysis demonstrated similar results, 44 whereas in a separate study, graft survival remained significantly higher in the machine perfusion group at year 3. 45 Kwiatkowski et al 46 reported a significant improvement in both graft survival and renal function at 5 years. In a separate study, DGF and cold ischemia time more than 24 hours were associated with a reduction in graft survival; however, patients with DGF but without AR did not experience an inferior graft survival rate.…”
Section: Early Ischemic Injury and Dgf In Kidney Transplantationmentioning
confidence: 99%
“…This report, however, places a primary focus on graft mortality, which, putatively for statistical reasons, has not been the primary endpoint in most of the controlled studies and, hence, might not come up directly with significant results. Nonetheless, in the latest randomized controlled study on kidneys donated after brain death, the 3-year study graft survival after machine perfusion was superior to that after cold storage, with differences being most pronounced for kidneys recovered from expanded criteria donors [39]. As far as delayed graft function and organ quality might be taken as clinically relevant outcome characteristics, the advantages of HMP over cold storage seem to be widely accepted, and renal preservation by machine perfusion has become an established alternative in many countries.…”
Section: Aerobiosismentioning
confidence: 99%